Structural Aspects of Multistep Phosphorelay-Mediated Signaling in Plants - Pekárová, Blanka; Szmitkowska, Agnieszka; Dopitová, Radka; Degtjarik, Oksana; Žídek, Lukáš; Hejátko, Jan (Molecular plant, 2016)
The multistep phosphorelay (MSP) is a central signaling pathway in plants integrating a wide spectrum of hormonal and environmental inputs and controlling numerous developmental adaptations. For the thorough comprehension of the molecular mechanisms underlying the MSP-mediated signal recognition and transduction, the detailed structural characterization of individual members of the pathway is critical. In this review we describe and discuss the recently known crystal and nuclear magnetic resonance structures of proteins acting in MSP signaling in higher plants, focusing particularly on cytokinin and ethylene signaling in Arabidopsis thaliana. We discuss the range of functional aspects of available structural information including determination of ligand specificity, activation of the receptor via its autophosphorylation, and downstream signal transduction through the phosphorelay. We compare the plant structures with their bacterial counterparts and show that although the overall similarity is high, the differences in structural details are frequent and functionally important. Finally, we discuss emerging knowledge on molecular recognition mechanisms in the MSP, and mention the latest findings regarding structural determinants of signaling specificity in the Arabidopsis MSP that could serve as a general model of this pathway in all higher plants.
Keywords: Plant Proteins; Cytokinins; signální transdukce; Signal Transduction; ethyleny; Arabidopsis; Ethylenes; multistep phosphorelay; response regulator; rostlinné proteiny; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; structure; histidine kinase; phosphotransfer protein; cytokininy